IDENTIFYING PERFORMANCE ASSURANCE CHALLENGES FOR SMART MANUFACTURING - Helu, Moneer (Manuf Lett, 2015)
Smart manufacturing has the potential to address many of the challenges faced by industry. However, the manufacturing community often needs assistance to leverage available technologies to improve their systems. To assure the performance of these technologies, this paper proposes a shared knowledge base that collects problem areas, solutions, and best practices for manufacturing technology. An Implementation Risk Assessment Framework (IRAF) is also described to identify the primary weaknesses of technologies in specific manufacturing contexts. Such approaches have the potential to stimulate new ideas and drive standardization activities critical to scale up and deploy smart manufacturing technologies successfully and quickly.